Männer mit Makel. Männlichkeiten und gesellschaftlicher Wandel in der frühen Bundesrepublik - Gotto, Bernhard (Zeitgeschichte im Gespräch, 2017)
The transformation of West German society in the long 1950s led to changes in society`s understanding of masculinity. Men who were different &#8211 disabled war veterans, the homeless, homosexuals &#8211 were under pressure to conform. This book tells the stories of men who were flawed, expounds on the crisis of masculinity, and illuminates the forces that promoted and inhibited greater life-style diversity.